Characterization of self-assembled structure of discotic liquid crystal molecules using small-angle X-ray scattering and computer simulation methods based on intermolecular interactions - Gihm, Se Hoon; Kim, Bong Gi; Kim, Sehoon; Seo, Jangwon; Park, Soo Young; Park, Chong Rae (ELSEVIER SCIENCE BV, 2010)
This study aimed at elucidating the self-assembly structure of newly synthesized three-armed discotic liquid crystal molecules (DLCs) which give rise to small-angle X-ray scattering (SAXS) profiles that have difficulties in the direct determination of the symmetry of long-range intercolumnar lattice. The self-assembly structure of newly synthesized two analogues of DLCs, viz. 1,3,5-tris[2-(4-dodecyloxyphenyl)-oxadiazol-5-yl]benzene (TDOB) and 1,3,5-tris[2-(3,4,5-tris-dodecyloxyphenyl)-oxadiazol-5-yl]benzene (TTDOB), being discerned only in the number of dodecyloxyphenyl tails on each oxadiazol arm, were elucidated by comparative analyzes between experimentally observed SAXS profiles and those generated from a computational method. TTDOB molecules exhibited a typical SAXS profile of a hexagonal columnar mesophase, but TDOB molecules showed an ambiguous one hard to analyze. We found that, in TDOB molecules, the low degree of branching caused the localized conjugated electrons, which leads to weakening of interdisc interactions of core part and loosing the packing of disc molecules. And the free space between arms, afforded by a single branch on each arm, and electrostatic interactions between opposite charges on neighboring molecules which come from the localized electrons, allow TDOB columns to pack more closely than the disc diameter, then to form an interdigitated columnar structure. Such self-assembly structure is thought to be the result of the balance of various intermolecular interactions, so the self-assembly structures were tried to explain through a relative contribution of each intermolecular interaction component, that is, individual interaction energy values that we can calculate. With our proposed approaches, it is expected to widen our understanding of the self-assembly structures of various materials including DLCs. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: POWDER DIFFRACTION DATA; COLUMNAR; ORIGIN; HEXABENZOCORONENE; POLYMERIZATION; DERIVATIVES; FABRICATION; FIBERS; PHASE